2010
DOI: 10.1007/s00383-010-2556-y
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic lobectomy for congenital cystic lung diseases in neonates and small infants

Abstract: Thoracoscopic lobectomy for congenital cystic lung diseases in neonates was practicable, with good esthetic results. Dissection was easier with significantly less blood loss in patients without adhesions, even in neonates. However, this procedure necessitated highly skilled endoscopic maneuvers within a small working space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 13 publications
3
35
0
1
Order By: Relevance
“…11 Others have clearly documented the issues involved with trying to operate on these lung lesions using thoracoscopy once the infant has already had a clinical chest infection. Kanenko et al 12 documented a higher complication rate in those patients who were diagnosed after a chest infection and underwent a thoracoscopic lobectomy compared with those diagnosed prenatally and operated on prior to any clinical infections. Garrett-Cox et al 13 found that 83% of patients converted to open surgery had had a previous chest infection.…”
Section: Discussionmentioning
confidence: 98%
“…11 Others have clearly documented the issues involved with trying to operate on these lung lesions using thoracoscopy once the infant has already had a clinical chest infection. Kanenko et al 12 documented a higher complication rate in those patients who were diagnosed after a chest infection and underwent a thoracoscopic lobectomy compared with those diagnosed prenatally and operated on prior to any clinical infections. Garrett-Cox et al 13 found that 83% of patients converted to open surgery had had a previous chest infection.…”
Section: Discussionmentioning
confidence: 98%
“…The "steep learning curve" for such procedures is inherent in the three technical difficulties accompanying pediatric thoracoscopy as follows: achieving single lung ventilation, maintaining vasculature control, and operating with minimal work space [15,16,20]. Following Rothenberg's descriptions of pediatric thoracoscopic pulmonary resections [14], a number of studies have deemed this procedure safe and feasible [12,18,25,28,29]. Furthermore, advocates of thoracoscopic management of BPM cite many salient advantages.…”
Section: Discussionmentioning
confidence: 96%
“…Most surgeons performing pediatric VATS lobectomy have avoided the use of surgical staplers in smaller infants due to the large dimensions of the applicator and cartridge that limit their applicability. Combinations described in the literature include the use of manual intracorporeal suturing for bronchial closure along with vessel-sealing of the pulmonary vasculature [1,3] or the use of 5 mm endoscopic clips on the bronchus [2,3]. Although intracorporeal suturing techniques have been demonstrated to have similar leak pressures to endoscopic stapling devices, the increased surgical time may result in increased morbidity and cost associated with surgery [12,13].…”
Section: Discussionmentioning
confidence: 97%